The Evolution of Clostridium difficile Infection in Cancer Patients: Epidemiology, Pathophysiology, and Guidelines for Prevention and Management - Khan, Areej; Raza, Shahzad; A. Batul, Syeda; Khan, Monis; Aksoy, Tulay; A. Baig, Mahadi; J. Berger, Barbara (Recent Patents on Anti-Infective Drug Discovery, 2012)
Clostridium difficile infection (CDI) has emerged as a significant challenge to the healthcare system. The availability of anti-cancer chemotherapeutic regimens has contemporaneously resulted in a larger population of patients who are susceptible to CDI. The outbreak of a novel, hypervirulent, resistant strain, NAP-1/027 as well as resistance to antibiotic therapy have further contributed to an increase in prevalence as well as in disease severity. Recent data show high fatality rates in cancer patients with CDI. In this review, we have discussed the incidence, epidemiology, pathophysiology, clinical signs and symptoms and therapeutic guidelines for patients who are on chemotherapy and present with CDI and highlighted clinical reports documenting severe CDI associated with chemotherapeutic agents such as methotrexate, 5FU, cisplatin, carboplatin, paclitaxel, vinorelbine and cyclophosphamide. The review article also has the discussion of patents pertaining to infections caused by Clostridium difficile in cancer patients. We underscore the urgent need for early recognition and diagnosis of CDI in cancer patients and for the design and implementation of randomized clinical trials of new treatment modalities in the management of chemotherapy- associated CDI.
Keywords: hypervirulent strain NAP-1/027